HUBUNGAN KEBIJAKAN SISTEM ZONASI TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Hidapenta, Detania; Dwiputri, Fira Ayu; Amaliyah, Sania (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research was motivated by enacting regulations regarding the zoning-based New Student Admission system in various schools in Indonesia. Meanwhile, the purpose of this research is to find out whether there is a relationship between the zoning system policy set by the government in PPDB on children's learning motivation and to find definite answers regarding the pros and cons that occur among the general public. In analyzing this, we use literature study as a research method, namely looking for various literature related to our research that is sourced from multiple media, both online and offline. Literature collection begins by searching for literature that discusses the zoning system and then on learning motivation in elementary schools, which includes definitions and characteristics. In searching for literature studies, prioritize the most recent year of publication. After collecting the literature, the relationship between zoning policies and the learning motivation of elementary school students. This study's results indicate a connection between the zoning policy in PPDB and the level of student motivation in elementary schools.